Think globally sabotage locally. How and why European companies are funding climate change deniers and anti-climate legislation voices in the 2010 US Senate race (Brussels, 2010)
"CAN Europe new report based on an analysis of publicly available campaign finance records, definitively proving that polluting European companies are funding climate legislation blockers in US politics. Their overseas support is all the more galling because the same companies argue that additional emissions reductions in Europe cannot be pursued until the United States takes action. “It’s disturbing that these European polluters fund anti-climate crusaders in the US while simultaneously fighting against strong climate legislation in Europe,” said Tomas Wyns, CAN Europe Senior Policy Officer. “This newly released data proves the anecdotal rumours about European companies that have been circulating for some time.”